Implementasi Project Based Learning Untuk Meningkatkan Keterampilan Kolaborasi Siswa Pada Materi Tata Surya - Ressa Novinta Sari; Atiningsih (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2023)
This research is a classroom action research which aims to determine the improvement of students' collaboration skills by using Project Based Learning learning model. This research was conducted in class VII E of SMP Negeri 29 Semarang in the even semester of the 2022/2023 school year with a total of 34 students. This research was conducted in two cycles. Data collection was carried out by direct observation during the learning process. The data obtained were then analyzed using descriptive statistical analysis, where the indicator of the success of this study was an increase in the average student collaboration skills in each cycle. The results showed that in the first cycle, an average percentage score of students' collaboration skills was obtained by 54%. Whereas in cycle II there was an increase with an average percentage of student collaboration skills scores of 74%. It can be concluded that the use of Project Based Learning learning models can improve students' collaboration skills